2011
DOI: 10.1089/neu.2010.1613
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin D-Sensitive Mitochondrial Permeability Transition in Adult Human Brain and Liver Mitochondria

Abstract: The mitochondrial permeability transition (mPT) is considered to be a major cause of cell death under a variety of pathophysiological conditions of the central nervous system (CNS) and other organs. Pharmacological inhibition or genetic knockout of the matrix protein cyclophilin D (CypD) prevents mPT and cell degeneration in several models of brain injury. If these findings in animal models are translatable to human disease, pharmacological inhibition of mPT offers a promising therapeutic target. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 66 publications
4
12
0
1
Order By: Relevance
“…mPT has been demonstrated across many species, including mitochondria from human cells49, rodents21, fish50 and yeast51. To confirm the screening data and demonstrate consistent compound pharmacology in human samples, mitochondria were isolated from HeLa S3 cells and Ca 2+ retention capacity assessed.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…mPT has been demonstrated across many species, including mitochondria from human cells49, rodents21, fish50 and yeast51. To confirm the screening data and demonstrate consistent compound pharmacology in human samples, mitochondria were isolated from HeLa S3 cells and Ca 2+ retention capacity assessed.…”
Section: Resultsmentioning
confidence: 90%
“…To date, only CypD has been truly agreed by numerous independent laboratories as being a critical regulator of pore opening, with substantial genetic and pharmacological studies having identified the role of CypD in potentiating pore opening212549. Most mPTP inhibitors reported in the literature, such as NIM-811, CsA and SfA desensitize the pore to Ca 2+ -induced opening, through inhibition of CypD243052.…”
Section: Discussionmentioning
confidence: 99%
“…In energized mitochondria, stabilization of the c conformation of the ANT (as it is by CAT) sensitizes the MPT to calcium. Also, oxidative stress activates the MPT by inhibiting ADP binding to the ANT and enhancing CypD-ANT interaction, decreasing the sensitivity of the calcium trigger [66]. Thus, inhibition of ATP/ADP translocation sensitizes mitochondria to MPT.…”
Section: Discussionmentioning
confidence: 99%
“…And mPTP deregulation is related with an increase of cell death. Due to this, the compounds that bind to Cyp D structure, could constitute an interesting tool for the treatment of many diseases where mitochondria are implicated, such as ischemic insults, muscular dystrophies, multiple sclerosis, amyotrophic lateral sclerosis and Alzheimer's disease (AD) while others [10].…”
Section: +mentioning
confidence: 99%